Phytochemical, Pharmacological Activities and Ayurvedic Significances of Magical Plant Mimosa pudica Linn - Kumar, Vijay (Mini-Reviews in Organic Chemistry, 2021)
Mimosa pudica Linn is an integrated part of the Traditional Medicines Systems of India, China, Africa, Korea and America. It has been used for centuries in traditional medicines to cure different diseases like fever, diabetes, constipation, jaundice, ulcers, biliousness, and dyspepsia. It is an essential ingredient of a wide class of herbal formulations. To assess the scientific evidence for therapeutic potential of Mimosa pudica Linn and to identify the gaps for future research, the available information on the ethno-medicinal uses, phytochemistry, pharmacology and toxicology of Mimosa pudica Linn was collected via a library and electronic searches in Sci-Finder, PubMed, Science Direct, Google Scholar for the period, 1990 to 2020. In traditional medicinal systems, a variety of ethno- medicinal applications of Mimosa pudica Linn have been noticed. Phytochemical investigation has resulted in the identification of 40 well known chemical constituents, among which alkaloids, phenols and flavionoids are the predominant groups. The crude extracts and isolates have exhibited a wide spectrum of in vitro and in vivo pharmacological activities including anti-cancer, antiinflammation, osteoporosis, neurological disorders, hypertension, etc. To quantify the Mimosa pudica Linn and its formulations, analytical techniques like HPLC and HPTLC have shown dominancy with a good range of recovery and detection limit. Mimosa pudica Linn is the well-known herb since ancient time. The pharmacological results supported some of the applications of Mimosa pudica Linn in traditional medicine systems. Perhaps, the predominance of alkaloids, phenols and flavionoids are responsible for the pharmacological activities the crude extracts and isolates of Mimosa pudica Linn. Further, there is a need to isolate and evaluate the active chemical constituents of Mimosa pudica Linn having significant medicinal values. In the future, it is important to study the exact mechanism associated with the phytochemicals of Mimosa pudica Linn especially on anti-cancer activities. Notably, toxicity studies on Mimosa pudica Linn are limited, which are to be explored in the future for the safe application of Mimosa pudica Linn and its formulations.
Keywords: herbal medicines